1996
DOI: 10.1254/jjp.72.247
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine for Reversal of Hemorrhagic Shock in Rabbits

Abstract: ABSTRACT-The potential use of adenosine in the treatment of hemorrhagic shock was evaluated in rabbits. Hemorrhagic shock was induced by bleeding the animals to a mean arterial blood pressure of 30-35 mmHg that was maintained for 2 hr. The intravenous infusion of 300 pg/kg/min adenosine for 1 hr, after reinfusion of the shed blood, was found to be capable of increasing the survival rate of rabbits subjected to hemorrhagic shock. In shocked rabbits, adenosine profoundly improved the postreinfusion depressed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…34 We did not compare the LSFG measurements with data obtained by these methods. Finally, we used heparinized blood for the blood-return phase, whereas some experimental animal models used a balanced hydroxyethyl starch solution, 5 Ringer's lactate solution, 35 or normal saline 36 for the resuscitation state. In the present study, we did not compare the effects on ocular and systemic hemodynamics based on the resuscitation fluid.…”
Section: Discussionmentioning
confidence: 99%
“…34 We did not compare the LSFG measurements with data obtained by these methods. Finally, we used heparinized blood for the blood-return phase, whereas some experimental animal models used a balanced hydroxyethyl starch solution, 5 Ringer's lactate solution, 35 or normal saline 36 for the resuscitation state. In the present study, we did not compare the effects on ocular and systemic hemodynamics based on the resuscitation fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results with systematically injected adenosine are difficult to interpret, because the half-life of injected adenosine in the plasma is very short (1-2 secs) owing to several mechanisms limiting its availability in the extracellular space (45)(46)(47). Nevertheless, intravenous infusion of adenosine for 1 hr after resuscitation increased the survival rate of rabbits subjected to hemorrhagic shock, which occurred despite the fact that adenosine depressed both MAP and heart rate in these animals (48). Intraperitoneal administration of adenosine protected organs and improved survival after volumecontrolled hemorrhagic shock in rats (49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that both endogenous adenosine and exogenous adenosine protect organs against from HS (42)(43)(44)(45). However, it is not well understood which receptor (s) mediate this protection.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the ENT1/ENT2 blocker dipyridamole, which increases endogenous adenosine levels, was protective in both rat (43) and canine (44) models of HS. Like endogenous adenosine, exogenously injected adenosine is protective, as it increased cardiac contractility and the survival rate of rabbits when administered after resuscitation from shock (45). The receptor(s) mediating the protective effects of adenosine are not well characterized.…”
Section: Introductionmentioning
confidence: 99%